Knowing My World: An English Learning Module Development with Multimodality and Deep Learning Approach - Haiyudi Haiyudi; Iful Rahmawati Mega; Dewi Agustin; Nurul Qomariyah; Zahra Herani; Sitthipon Art-in (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2025)
The new policy of the Indonesian educational system aims to engage all stakeholders, including teachers, in continually improving their capacity and adapting to changes. This study aims to develop an English language learning module titled